Synthesis, Spectral, Structural and Antimicrobial Studies of Silver Nanoparticles and Ag(I) Complex of 2-Mercaptobenzothiazole - Ahmed, Alya’a Jabar; Ali Alsammarraie, Abdulkareem Mohammed (Asian Journal of Chemistry, 2018)
In the present study, Ag(I) complex is synthesized by reacting silver nitrate with ligand (2-mercaptobenzothiazole) in a 1:2 mole ratio. Furthermore, silver nanoparticles were prepared by the reduction of AgNO3 using 2-mercaptobenzothiazole in dilute aqueous sodium citrate buffer solution. The Ag(I) complex are characterized by elemental analyses, flame atomic absorption, thermogravimetric analyses, molar conductance and magnetic susceptibility, UV-visible as well as FTIR spectroscopy. Analyses, linear geometry is suggested for the Ag(I) complex. The prepared nanoparticles are characterized using X-ray diffraction, scanning electron microscopy, energy dispersive microscopy, atomic force microscopy, vibrational and electronic spectroscopy. X-ray diffraction analysis revealed that silver nanoparticles with fcc crystal structure. The SEM micrographs indicated that the morphology is nearly rods shaped structure with an average diameter of about 100 nm. Biological activities of the ligand and its Ag(I) complex and silver nanoparticles are tested against Staphylococcus aureus, Escherichia coli bacteria and Candida albicans, Candida tropicalis fungi. It was found that both Ag(I) complex and silver nanoparticles have antimicrobial activities.